Winding Design and Efficiency Analysis of a Nine-Phase Induction Machine from a Three-Phase Induction Machine - Ariel Fleitas; Magno Ayala; Osvaldo González; Larizza Delorme; Carlos Romero; Jorge Rodas; Raul Gregor (Machines, 2022)
Multiphase machines are a hot research topic in control theory and industrial applications such as electric cars. However, the availability to buy them in the market is limited or null. For this reason, it is common to rewind it from a three-phase commercial machine. In this context, the aim of this paper is two-fold. First, to introduce a straightforward procedure to rewind a nine-phase induction machine from a three-phase one. For that purpose, a study of the three-phase induction motor was performed, which included selecting a new winding design, calculating stator coils, and simulating tests with ANSYS Maxwell software to validate the design. Secondly, a performance analysis comparing the power losses through experimental tests performed to obtain the electrical parameters of both nine-phase and three-phase topologies is presented.